Proceedings of the International Conference on Sustainable Innovation on Health Sciences and Nursing (ICOSI-HSN 2022) 2022
DOI: 10.2991/978-94-6463-070-1_31
|View full text |Cite
|
Sign up to set email alerts
|

Dental Patient Utilization During the Covid-19 Pandemic at Mungkid Primary Health Centre in 2020

Abstract: In early 2020, there was a discovery of the Covid-19 virus that could transmit very quickly through droplets, so it was eventually designated a pandemic. Dentists are always in contact with saliva and blood. They are susceptible to droplets and aerosols, so there are regulations regarding dental care services during a pandemic that can affect dental patient visits. This study aims to determine the utilization of dental patients during the Covid-19 pandemic at the Mungkid Primary Health Centre. The type of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…During the study duration of 15 months, findings revealed that dental care was the main reason for extraction of teeth followed by periodontitis. 8 Surgical extraction of impacted teeth were done more in female patients, while extractions for orthodontic treatment were more in males. This observation differed from a similar study done in this institute back in 2011 wherein surgical extraction of wisdom teeth was done more in male patients, while extraction for orthodontic reasons were more in female patients.…”
Section: Resultsmentioning
confidence: 99%
“…During the study duration of 15 months, findings revealed that dental care was the main reason for extraction of teeth followed by periodontitis. 8 Surgical extraction of impacted teeth were done more in female patients, while extractions for orthodontic treatment were more in males. This observation differed from a similar study done in this institute back in 2011 wherein surgical extraction of wisdom teeth was done more in male patients, while extraction for orthodontic reasons were more in female patients.…”
Section: Resultsmentioning
confidence: 99%